To solve the quadratic equation \((x - 7)^2 = 11\), we'll first find the solutions by isolating \(x\).
-
Take the square root of both sides: \[ (x - 7) = \pm \sqrt{11} \]
-
Solve for \(x\):
-
For the positive case: \[ x - 7 = \sqrt{11} \implies x = 7 + \sqrt{11} \]
-
For the negative case: \[ x - 7 = -\sqrt{11} \implies x = 7 - \sqrt{11} \]
-
So the two solutions to the equation are:
- \(x_1 = 7 - \sqrt{11}\) (the smaller solution)
- \(x_2 = 7 + \sqrt{11}\) (the larger solution)
Now, let's fill in the table with the necessary evaluations.
-
Substituting \(7 - \sqrt{11}\): \[ (7 - \sqrt{11}) - 7 = -\sqrt{11} \] Squaring this gives: \[ (-\sqrt{11})^2 = 11 \quad \text{(True statement)} \]
-
Substituting \(7\): \[ 7 - 7 = 0 \] Squaring this gives: \[ 0^2 = 0 \quad \text{(not equal to 11, False statement)} \]
-
Substituting \(7 + \sqrt{11}\): \[ (7 + \sqrt{11}) - 7 = \sqrt{11} \] Squaring this gives: \[ (\sqrt{11})^2 = 11 \quad \text{(True statement)} \]
-
Substituting \(11 - 7\) (which is \(4\)): \[ 4 - 7 = -3 \] Squaring this gives: \[ (-3)^2 = 9 \quad \text{(not equal to 11, False statement)} \]
In summary:
- The smaller of the two solutions is \(x = 7 - \sqrt{11}\).
- The larger of the two solutions is \(x = 7 + \sqrt{11}\).
Finally, the answers are:
- The smaller of the two solutions is \(x = 7 - \sqrt{11}\).
- The larger of the two solutions is \(x = 7 + \sqrt{11}\).